APPLICATION OF SOCIAL NETWORKS BY UNIVERSITY LIBRARIES OF UKRAINE - Romanuha, Zoia V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article analyzes the major trends and ways to further improvement the interaction between Ukrainian university libraries and social networks.